Analysis of the Influence of Leadership and Competency Training on Employee Performance - Joko Purnomo; Sujarwo Sujarwo; Yudan Hermawan (Electronic Journal of Education, Social Economics and Technology, 2025)
The purpose of this study is to find out the performance of employees who are influenced by the contribution of training and competence. The research method uses quantitative with the process of collecting field observation data, interviewing and distributing questionnaires. The research sample had a total of 43 respondents. The results obtained on the training variable can be seen with the number of T-calculations of 4,945 and the T-table with a value of 2,019 obtained results (4,945 2,019) and in significant results (0,000 0.05). In competence, the number of T-calculations of 2,117 and the T-table of 2,019 were obtained results (2,117 2,019) and significant results (0.041 0.05). From these results, it can be concluded that employee performance is affected by training. In addition, another conclusion is that the contribution of training affects significantly and positively to employee performance, as well as employee performance which is influenced by competence with significant and positive influences. In the result of F sebsar 48,357 with significance obtained (0.000 005). With the result that there is a Ho that is rejected and there is a Ha that is accepted with a statement of the training and competency variables simultaneously (simultaneously) has a significant influence and has a positive impact on employee performance.